2017
DOI: 10.1111/pbr.12534
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci underlying soybean seed tocopherol content with main additive, epistatic and QTL × environment effects

Abstract: Soybean (Glycine max [L.] Merrill) seeds are a major source of tocopherols (Toc), which could significantly improve immune system health of human and prevent or treat many serious diseases. Selection for higher Toc contents of seeds could increase nutritional value of soybean‐derived food, laying on an important breeding goal for many soybean breeders. The present objectives of the work were to evaluate various genetic effects of QTL associated with individual and total Toc content based on a RIL population (“… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
(63 reference statements)
0
11
0
Order By: Relevance
“…The GWAS based on natural populations was an alternative method of linkage analysis and was widely used in the analysis of important crop traits (Rakotoson et al, 2021;Yuan et al, 2021). Compared with linkage analysis, the range of phenotypic variation in single analysis was increased by GWAS, which was due to the high natural variation caused by the accumulation of historical reorganization events in the natural population (Liu et al, 2017). The development of genome sequencing and SNP genotyping technology has promoted the applicability of the GWAS in soybean research; thus, it was particularly important to select an appropriate model for effective and accurate mapping according to research needs (Kim et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The GWAS based on natural populations was an alternative method of linkage analysis and was widely used in the analysis of important crop traits (Rakotoson et al, 2021;Yuan et al, 2021). Compared with linkage analysis, the range of phenotypic variation in single analysis was increased by GWAS, which was due to the high natural variation caused by the accumulation of historical reorganization events in the natural population (Liu et al, 2017). The development of genome sequencing and SNP genotyping technology has promoted the applicability of the GWAS in soybean research; thus, it was particularly important to select an appropriate model for effective and accurate mapping according to research needs (Kim et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a variety of new methods have been proposed, with the rapid development of computing technology and sequencing technology ( Wang et al., 2016 ; Huang et al., 2018 ; Xiao et al., 2021 ; Li et al., 2022a ). Although this propelled much of the practicability of GWAS, it is particularly important to select the appropriate sequencing method and suitable model for improving the positioning efficiency according to the research needs ( Liu et al, 2017 ; Kim et al, 2021 ). For this study, we adopted six models (GLM, MLM, CMLM, BLINK, FarmCPU, and 3VmrMLM), to conduct GWAS of Toc content in soybean seeds.…”
Section: Discussionmentioning
confidence: 99%
“…Shaw et al (2017) [15] found nine and five QTLs, by single marker analyses and interval mapping, respectively, for α-Toc contents in a cross with OAC Bayfield and a low α-Toc OAC Shire across three locations over 2 yrs, of which the QTL tagged by Satt117 (Chr15) had the largest effect, accounting for up to 32% of the phenotypic variation. Liu et al (2017) [13] reported a total of 18 QTLs for α-Toc contents in an RIL population of a cross with the Chinese high α-Toc local variety Beifeng 9, of which four QTLs in Chr15 had stable and significant additive effects across six environments. These studies similarly detected QTLs in Chr15, although the candidate genes remained undetermined.…”
Section: Discussionmentioning
confidence: 99%